1998
DOI: 10.1016/s0014-5793(98)01426-4
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining and characterization of EF‐hand mutants of recoverin

Abstract: Several EF-hand recoverin mutants were obtained and their abilities to bind to photoreceptor membranes and to inhibit rhodopsin kinase were determined. The mutants with the`spoiled' 2nd, 3rd or (2nd+3rd) EF-hand structures did not act upon the kinase activity in the W WM range of Ca 2+ concentrations. Mutations of the 4th EF hand, which`repaired' its Ca 2+ -binding activity, resulted in recoverin with three`working' Ca 2+ -binding sites. The latter mutant inhibited rhodopsin kinase even more effectively than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…In the first, a myristoylated calcium-binding mutant still associated weakly with reconstituted ROS membranes and even exhibited limited inhibition of RK (34). In the second, Rv was found in lipid rafts even in the presence of EGTA (35).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the first, a myristoylated calcium-binding mutant still associated weakly with reconstituted ROS membranes and even exhibited limited inhibition of RK (34). In the second, Rv was found in lipid rafts even in the presence of EGTA (35).…”
Section: Discussionmentioning
confidence: 98%
“…Our results have direct implications for the mechanism of Rv action. The studies that led to the calcium-myristoyl switch model of Rv regulation utilized recombinant myristoylated Rv for structural analysis (4,8,26) or for in vitro association with reconstituted ROS membranes or membrane vesicles (27,34). The only pertinent study employing Rv in its natural environment showed the protein to remain associated with ROS lipid rafts even upon calcium chelation (35).…”
Section: Discussionmentioning
confidence: 99%
“…EF-hand 2 seems to be critical for the control of rhodopsin kinase activity (31). Alekseev et al (27) found no inhibition of rhodopsin kinase by myristoylated Rc E85Q in the range of 1 to 100 M Ca 2ϩ . However, a small fraction of Rc E85Q (25%) can bind to membranes.…”
Section: Ca 2ϩ -Myristoyl Switch Of Recoverin 50370mentioning
confidence: 97%
“…To understand the mechanism of the Ca 2ϩ -myristoyl switch in greater molecular detail, we used recoverin mutants with impaired EF-hand Ca 2ϩ -binding sites (27). For this purpose, we introduced the substitutions E85Q (mutant Rc E85Q ) and E121Q (mutant Rc E121Q ) in EF-hand 2 and EF-hand 3 of recoverin, respectively, because we know that substitutions in the Z position of the loop of the EF-hand motif decrease the affinity of the Ca 2ϩ -binding site for Ca 2ϩ by about 1000-fold (28,29).…”
mentioning
confidence: 99%
See 1 more Smart Citation